Tragic hero and hero tragedy: reimagining Oedipus the King as Jingju (Peking opera) for the Chinese stage. (12th June 2018) - Qi, Shouhua; Zhang, Wei
Abstract: Although the 2009 jingju (Peking opera) adaptation of Oedipus the King does not completely indigenize the Greek classic, i.e. relocating it to a time and place in Chinese culture and history, it Sinicizes the names of characters and places and retools the plot so it would better appeal to Chinese audiences. More than anything, this jingju remake of the Greek classic, as Chinese adaptations of Greek classics typically do, demythologizes and thus deemphasizes the agency of gods, Greek or their native divination substitutes, by way of highlighting the 'heroism' of the titular protagonist. What results is a Sinicized Oedipus, virtuous 1 and well-beloved, whose nobility is sustained to the very end without being 'flawed' by excessive pride, a fiery temper or paranoia. He remains devoted to the public good — to bring deliverance to his people — instead of being consumed by a headstrong quest for personal truth although the two, the public and the personal, are painfully intertwined. This reinterpretation of what is considered a quintessentially classic Greek tragedy as a 'hero tragedy' is overdetermined by the aesthetics of jingju, the sociocultural needs of the Chinese people today, and the challenges and possibilities of such transcultural adaptations, thus engendering interesting and enriching intertextual reverberations across cultures.